Hypercoagubility: An Updated Overview for Healthcare Providers - Jaafari, Abdullah Siddiq Ahmed; Alajmi, Khaled Hadi Ali; Althabaity, Ahmed Misfer; Salem, Khalid Shayim Alsharari; Alhargan, Mohammed Saleh; Alotaibi, Hissah Faihan Ayad; Almutairi , Najla Alhumaidi; Alanazi, Samar Mnwer; Almutairi, Fayez Nukhaylan; Alazmi, Abdullah Hamdan Khidhr; Alotaibi, Mamdoh Abdullah (Journal of Ecohumanism, 2024)
Background: Hypercoagulability, or thrombophilia, is a pathological state characterized by an increased tendency for blood clot formation, leading to conditions such as venous thromboembolism (VTE), arterial thrombosis, and thromboembolism. This condition arises from a disruption in the balance between pro-coagulant and anticoagulant factors, influenced by both inherited and acquired risk factors. The understanding of hypercoagulability has evolved significantly since the early 20th century, with key discoveries such as antiphospholipid syndrome, factor V Leiden mutation, and deficiencies in proteins C and S contributing to improved diagnosis and management. Aim: This article aims to provide healthcare providers with an updated overview of hypercoagulability, including its etiology, epidemiology, pathophysiology, diagnostic approaches, and management strategies, to enhance the prevention and treatment of thrombotic disorders. Methods: The review synthesizes current literature on hypercoagulability, focusing on the interplay between genetic and environmental factors, the role of Virchow’s triad in thrombosis, and the clinical significance of various thrombophilic disorders. Diagnostic tools, risk assessment models, and treatment options, including anticoagulation therapy, are discussed in detail. Results: Hypercoagulability disorders are influenced by both inherited mutations (e.g., factor V Leiden, prothrombin G20210A) and acquired conditions (e.g., malignancy, inflammation, pregnancy). Thrombosis risk is further modulated by factors such as age, lifestyle, and comorbidities. Diagnostic approaches include thrombophilia screening and risk stratification tools, while management involves anticoagulation therapy tailored to individual patient risk profiles. Conclusion: Hypercoagulability is a multifactorial condition requiring a comprehensive understanding of its underlying causes and risk factors. Early diagnosis, risk stratification, and personalized treatment are essential to reduce morbidity and mortality associated with thrombotic disorders. Future research should focus on novel therapies and improved risk prediction models